Dataset on non-state actor participation in regional fisheries management organizations - Lisa M. Dellmuth; Matilda T. Petersson; Daniel C. Dunn; André Boustany; Patrick N. Halpin (Data in Brief, 2021)
In this article, we present and describe a new dataset of non-state actor participation in seven regional fisheries management organizations (RFMOs). The dataset contains institutional, economic and ecological variables relevant for non-state actor participation in RFMOs and for RFMO effectiveness. To code non-state actor participation and institutional factors, we quantify information from publicly available RFMO reports as well as data from the Policy IV dataset. We pair these data with existing datasets on ecological and economic factors from the RAM Legacy and the Sea Around Us databases. This article describes the data collection process and the coded variables in detail.